A new species of Scytalidium causing slippery scar on cultivated Auricularia polytricha in China. Issue 1 (2nd September 2014) - Peng, Weihong; He, Xiaolan; Wang, Yong; Zhang, Yong; Ye, Xiaojin; Jia, Dinghong; Guo, Yong; Gan, Bingcheng; Zheng, Chao; Yang, Zhirong; Sun, Qun
Abstract Slippery scar is one of the most destructive diseases encountered in the cultivation of Auricularia polytricha (hairy wood ear); however, the identity of the pathogenic agent has remained uncertain. This study was designed to identify the causative pathogen of slippery scar in A. polytricha and to investigate the taxonomic classification of the pathogen by morphological observations, in vivo pathogenicity tests, and molecular evidences of ITS and RPB2 sequences. The results showed that the pathogen was a new Scytalidium species, here named Scytalidium auriculariicola. Scytalidium auriculariicola was characterized by its rapid growth rate, the catenate conidia of variable size, and the pale brown to brown chlamydoconidia. Phylogenetic analyses based on internal transcribed spacer regions and RPB2 sequences on the pathogen isolated and related species supported that S. auriculariicola was a true Scytalidium species. It was congeneric with and close to Scytalidium lignicola, the type species of Scytalidium. However, it differed from the latter species in the size of conidia, 33 different nucleotide bases in ITS sequences and 30 different nucleotide bases in RPB2 sequences.